1991
DOI: 10.1136/bmj.302.6788.1299
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus: evidence for sexual transmission.

Abstract: Objective-To determine the prevalence of hepatitis C virus infection and associated risk factors in patients attending a genitourinary medicine clinic, as evidence for sexual transmission.Design-Seroprevalence estimated by reactivity in an enzyme immunoassay for antibodies to C100 protein with supplementary testing with a recombinant immunoblot assay and an assay for hepatitis C virus RNA.Setting-Outpatient genitourinary medicine clinic in central London.Patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(56 citation statements)
references
References 10 publications
2
54
0
Order By: Relevance
“…The most comparable study, by Okamoto and coworkers (4), examined 10 sets of primers and found that those derived from the 5' NC and the putative core gene region were equivalent in their ability to detect HCV RNA in 10 anti-HCV-positive sera from Japanese individuals. Other studies have demonstrated enhanced detection of HCV RNA with primers from the 5' NC region compared with those specific for other regions (6,39,40). Although these studies did not specifically address the factors discussed above, the results suggest that primers from the 5' end of the HCV genome are effective at detecting HCV RNA by PCR analysis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The most comparable study, by Okamoto and coworkers (4), examined 10 sets of primers and found that those derived from the 5' NC and the putative core gene region were equivalent in their ability to detect HCV RNA in 10 anti-HCV-positive sera from Japanese individuals. Other studies have demonstrated enhanced detection of HCV RNA with primers from the 5' NC region compared with those specific for other regions (6,39,40). Although these studies did not specifically address the factors discussed above, the results suggest that primers from the 5' end of the HCV genome are effective at detecting HCV RNA by PCR analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Several groups have examined the effectiveness of different primer sets in detecting HCV RNA by PCR (4,6,13,14,34,(39)(40)(41). The most comparable study, by Okamoto and coworkers (4), examined 10 sets of primers and found that those derived from the 5' NC and the putative core gene region were equivalent in their ability to detect HCV RNA in 10 anti-HCV-positive sera from Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although a study published in the early 1990s suggested that a higher prevalence of HCV infection in MSM (6.9%) compared with heterosexual subjects (1.0%) attending a genitourinary clinic in London was strong evidence of sexual transmission of HCV among MSM, the study did not account for a history of injection drug use. 18 A larger, more recent study in genitourinary clinics in the United Kingdom, using similar methods, found a low prevalence of anti-HCV among non-IDU, with the anti-HCV prevalence in MSM not significantly different from non-MSM (0.92% vs. 0.75%, PR 1.23; 95% CI 0.76, 1.98). 19 The prevalence of HCV infection among MSM in STD clinics has generally been found to be no higher than among heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although HCV viral RNA has been detected in the semen, the role of sexual, perinatal, and other possible nonparenteral routes of HCV transmission is still unclear (7)(8)(9), but from the available evidence this risk appears to be minimal (10). Indeed, even in the presence of acute infection, semen viremia is extremely low as evaluated by PCR (11)(12)(13)(14), suggesting a low risk of sexual transmission.…”
Section: Introductionmentioning
confidence: 99%